Retracted: Telemetry Data Compression Algorithm Using Balanced Recurrent Neural Network and Deep Learning - Intelligence and Neuroscience, Computational (Computational intelligence and neuroscience, 2023)
[This retracts the article DOI: 10.1155/2022/4886586.].